OPTIMIZATION OF BREASTFEEDING DURING THE COVID-19 PANDEMIC - Elsidianastika Trisnawati, Reineldis; Sedista Manggul, Makrina; Nova Nanur, Fransiska; Florentin Bebok, Christin; Wahyuningsih, Sri (LPPM Univ. Ibn Khaldun Bogor, 2022)
The covid-19 pandemic is a serious problem that is facing the whole world. The pandemic has caused social restrictions that cause concern and stress for many people. The results of preliminary studies conducted on several breastfeeding mothers stated that during the Covid-19 pandemic, there were many mothers' concerns about continuing the process of breastfeeding babies directly. According to global data, the rate of exclusive breastfeeding is quite low, which is only 41 percent. In Indonesia itself, based on Basic Health Research data in 2018, shows that the rate of exclusive breastfeeding only reaches 30.2 percent. The number of exclusive breastfeeding rates, which are small globally and in Indonesia, has worsened with the COVID-19 pandemic. To overcome this, people need to be given health education about the importance of breastfeeding during a pandemic and explain that the COVID-19 virus is not infected through breastfeeding. This community service activity has been carried out from February to April 2021. The results of this activity have a positive impact on the community, especially on breastfeeding mothers.